Dimensional stability properties of laminated veneer lumber made from oil palm trunk bonded with different cold set adhesives / Siti Noorbaini Sarmin, Othman Sulaiman and Rokiah Hashim - Sarmin, Siti Noorbaini; Sulaiman, Othman; Hashim, Rokiah (2011)
Dimensional stability properties of laminated veneer lumber (LVL) from oil palm trunk (OPT) bonded with three different cold set adhesives namely emulsion polymer isocyanate (I, 3-butadiene-styrene and vinyl acetate based) and polyvinyl acetate were investigated. Three-ply experimental LVL from OPT veneers were bonded using two adhesive spread levels; 250g/m2 and 500g/m2 for single glue line. Laminated veneer lumber from rubberwood was used as control. The dimensional stability properties investigated include dimensional changes associated with changes in relative humidity of 30 to 90 percent, hysteresis over a range of30 to 90 percent and durability against biological attack through soil burial. Amongst the three adhesives, OPT LVL manufactured with EPI (VAc) had the highest FSP and the least was experienced by OPTLVL bonded with PVA c. Totally, the magnitude of hysteresis was below l. 00 which in the average 0.69 to 0.82 for OPT LVL panels while rubberwood LVL, 0.81 to 0.94 respectively. Through the eight weeks study, it was found that most of the samples were degraded by termites and organism and by the end of eight weeks, there were mixed together with soil. LVL panels produced using EPI (SBR) was exhibited the highest percentage of weight loss compared to LVL bonded EPI (VAc) and PVAc respectively.